Penerapan Hukum dan Sanksi Tindak Pidana Pemerkosaan oleh Anak Dibawah Umur dalam Perspektif Hukum Pidana Islam - Athiyyatul Mufidah1; Zamroni Ishaq (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
: A criminal act is a violation of norms regarding disturbance of the rule of law intentionally or unintentionally committed by the perpetrator, where the imposition of a prison sentence against the perpetrator is necessary for the maintenance of legal order and also to ensure the interests of the general public. The rampant rape of minors, as happened in various regions in Indonesia, where the perpetrators were their own fathers to an ustadz who raped dozens of his students, children are the future of the nation who have the right to live and develop, so these rights must be protected, and there is no implementation Appropriate law against the perpetrators is the main focus where the application of sanctions is currently only limited to imprisonment for 5-15 years or life imprisonment even though there are opportunities for more severe punishments such as chemical castration and the death penalty. In the event that the crime of rape of a minor causes more than 1 person to be victimized, results in serious injury, mental disorder, infectious disease, disruption or loss of reproductive function, or the victim dies, the perpetrator shall be sentenced to death, life imprisonment or imprisonment for a minimum of 10 years and a maximum of 20 years.